Women’s Disability Studies – Sources and Chosen Aspects of Discourse - Wlazło, Marcin (Interdyscyplinarne Konteksty Pedagogiki Specjalnej, 2020)
The article presents the genesis of women’s disability studies as an academic and social activity of women with disabilities who pointed out that their experiences were ignored both in general disability studies and in the feminist discourse. The contemporary aspects of women’s disability studies are presented on the example of discourses on the body, violence against women with disabilities and their economic situation. The aim of the article is to present women’s disability studies in a context that goes beyond the analyses focused on Europe or the United States of America and broadens the area of interest to include the experiences of women with disabilities in the countries of the Global South.